Α2-adrenoceptor binding in Flinders-sensitive line compared with Flinders-resistant line and Sprague-Dawley rats. Issue 6 (23rd April 2015) - Lillethorup, Thea Pinholt; Iversen, Peter; Wegener, Gregers; Doudet, Doris Jeanne Marie; Landau, Anne Marlene
Abstract : Objectives: Disturbances in the noradrenergic system, including alterations in the densities of α2 -adrenoceptors, are posited to be involved in the pathophysiology of depression. In this study, we investigate the binding of α2 -adrenoceptors in regions relevant to depression in an animal model of depression. Methods: Using in vitro autoradiography techniques and the selective α2 -ligand, [ 3 H]RX 821002, we investigated the density of α2 -adrenoceptors in female Flinders-sensitive line (FSL) rats, a validated model of depression, and in two traditional control groups – female Flinders-resistant line (FRL) and Sprague-Dawley (SD) rats. Results: The α2 -adrenoceptor density was increased in most regions of the FSL rat brain when compared with SD rats (10% across regions). Moreover, the α2 -adrenoceptor density was further increased in the FRL rats compared with both FSL (10% across regions) and SD rats (24% across regions). Conclusions: The increase in α2 -adrenoceptor binding in cortical regions in the FSL strain compared with the SD control strain is in accord with α2 -adrenoceptor post-mortem binding data in suicide victims with untreated major depression. However, the differences in binding observed in the two control groups were unexpected and suggest the need for further studies in a larger cohort of animals of both sexes.